2022
DOI: 10.1097/gco.0000000000000783
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of endometrial receptivity and implantation failure

Abstract: Purpose of reviewTo succinctly review the basic mechanisms of implantation and luteal phase endometrial differentiation, the etiologies of impaired endometrial function and receptivity, and the current methods that exist to evaluate and treat impaired endometrial receptivity. Recent findingsHuman embryo implantation requires bidirectional communication between blastocyst and a receptive endometrium. Etiologies of impaired endometrial receptivity are varied. Some of these include delayed endometrial maturation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 104 publications
0
8
0
Order By: Relevance
“…Because our research was not focused on evaluating endometrial receptivity, we only performed endometrial biopsies for further diagnostics, for example, of unclear bleedings, not to assess endometrial receptivity. However, the improvement of EMT, corpus luteum function, and endometrial blood flow implies an increase in endometrial receptivity in many studies ( 19 , 20 ). Furthermore, in relevant studies, DKP showed more complex potential mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Because our research was not focused on evaluating endometrial receptivity, we only performed endometrial biopsies for further diagnostics, for example, of unclear bleedings, not to assess endometrial receptivity. However, the improvement of EMT, corpus luteum function, and endometrial blood flow implies an increase in endometrial receptivity in many studies ( 19 , 20 ). Furthermore, in relevant studies, DKP showed more complex potential mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial receptivity refers to the ability of the endometrium to “accept” the embryo for implantation within a specific timeframe of the secretory phase, and to provide an optimal environment for pregnancy development ( Bui et al, 2022 ). A recent systematic review and meta-analysis of studies examining pregnancy outcomes from embryos derived from non-autologous oocytes demonstrated a higher miscarriage rate and lower live birth rate in women with AMA, though the analysis included studies with variable definitions of AMA and a wide range of cutoffs ( Zhao J. et al, 2023 ).…”
Section: Insights From Human Clinical Studiesmentioning
confidence: 99%
“…The impact of female reproductive health on pregnancy rates and offspring has garnered significant attention. Female reproductive factors, such as ovarian development, oocyte maturation, estrous cycle, and embryo implantation, were influenced primarily by sex hormones, including progesterone, prostaglandin, and estrogen ( Innocenti et al, 2017 ; Bui et al, 2022 ). Sex hormones play crucial roles in the complex and interconnected processes of pregnancy and childbirth ( Zamberlam et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%